Morphogenesis in species Monarda fistulosa L. i Monarda citriodora L. in Southern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The article presents the results of studies of seed populations of Monarda fistulosa L. and Monarda citriodora L., grown in sub fescue-feather grass steppes of Ukraine steppe zone (territory of the State Enterprise «Research Farm «Novokahovske» Nikita Botanical Gardens-National Science Center, Kherson region, Ukraine). It has been identified four forms (3–12, 4–12, 5–12, 6–12) of the plants Monarda fistulosa of local reproduction that obtained by free pollination varieties copies ‘Premier’ and ‘Fortuna’. These forms differ in habit and number of shoots, flower color intensity, color and leaf form plate morphometric parameters of the plant and the timing of flowering . here forms were selected in Monarda citriodora (1–11, 2–12, 3–12) which differ in terms of early flowering, duration of flowering, degree of drought, habitus and the number of whorls of inflorescence. New forms of both species were selected for further breeding, further study and utilization in breeding.
Keywords: Monarda, Monarda fistulosa, Monarda citriodora, forma, seed population, Kherson region, Ukraine.